Preparation Of Chuhara-Like Product From Ber (Zizyphus Mauritiana Lamk.) Through Osmo-Air Drying Process (Applied Biological Research, 2011)
Studies on the preparation of ber chuhara through osmo-air drying  process were conducted at the Division of Post Harvest Technology,  SKUAST-J, Jammu. Before making chuhara, the ber (Zizyphus  mauritiana Lamk.) fruits were subjected to different pre-treatments, viz.,  lye peeling (5% NaOH for 5 min.), citric acid treatment (5% for 5 min.)  and KMS treatment (@ 4000 ppm for 12 h). Pretreated ber were dipped  different sugar concentrations of 40, 50, 60 and 70° Brix at 24, 48 and  72 h. The treated fruits were then dried at 522°C for 6 h in a dehydrator  till a chewable and appealing product was developed. Sensory evaluation  revealed that 70°Brix at 72 h gave best chuhara-like product from ber  through osmo-air drying process and could be an acceptable product.
Keywords: Ber; chuhara; osmo-air drying; sugar concentration; Zizyphus mauritiana